TEACHER’S QUESTIONING STRATEGIES IN EFL CLASSROOM INTERACTION - Eka Fatmawati; Andi Qashas Rahman; Murni Mahmud (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2020)
This paper aims to identify and investigate questioning strategies used by teachers in EFL classroom interaction The data were collected by qualitative research in 2015 from a university teacher of STKIP YPUP Makassar by using classroom observation and interview the teachers and students. To analyze the data, the researcher used three key stages by Miles and Huberman (1994) namely data reduction, data display, and conclusion drawing/verification. The findings show that the teacher applied questioning-planning strategies, question-controlling strategies, and nomination strategies. There was a new questioning strategy that was found, named endless-questioning strategy. The teacher applied his questioning strategies by asking questions to an individual student, pair students, and the whole class. The teacher mostly applied it to an individual student and the whole class rather than to pair students.